Air Temperature Variability in Illinois Based on Weather Station Records and the North American Regional Reanalysis from 1979 to 2006 - (:unkn) unknown (My University, 2017)
Spatial and temporal near-surface air temperature 21 variabilities and trends were analyzed for 30 locations in Illinois based on annual data derived from station records and the North American Regional Reanalysis (NARR) dataset from 1979 to 2006. A high correlation was found between the two datasets regarding interannual variability at most locations. Temperatures were generally higher at urban stations than non-urban stations while non-urban NARR data points showed higher temperatures than urban data points. The differences in medians were not statistically significant in either dataset. Significant positive temperature trends were found in the majority of the weather stations and in all NARR data points, with generally stronger trends with the NARR data. Observed trends from the station records were generally stronger in metropolitan areas and weaker for non-urban areas while the reanalysis data did not show a remarkable difference between urban and non-urban trends.
Keywords: temperature; Illinois; weather station; North American Regional Reanalysis